1994
DOI: 10.1209/0295-5075/25/6/002
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Dynamics of Photoexcited States in C 60

Abstract: We have measured the relaxation of photoexcited states in C60 using femtosecond excitation at energies corresponding to the h1u → t1u bandgap. Induced absorption with a fast 2 ps relaxation is observed, which has bimolecular kinetics indicative of exciton-exciton annihilation. The induced absorption is spectrally broad with peaks at 1.92 and 2.25 eV. These features are assigned to excited-state absorption from the t1u level to higher-lying hg excited states at ∼ 4.0 eV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…This time is much less than the ϳ2.5-ns intersystem crossing time we measure at lower exciton concentrations. Similar behavior has been previously suggested 19 for incompletely characterized films of C 60 and has also been discovered in model compounds of conjugated polymers. 2 Excess T 1 production at high concentrations may have ramifications for potential devices operating at high concentrations, such as polymeric lasers.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This time is much less than the ϳ2.5-ns intersystem crossing time we measure at lower exciton concentrations. Similar behavior has been previously suggested 19 for incompletely characterized films of C 60 and has also been discovered in model compounds of conjugated polymers. 2 Excess T 1 production at high concentrations may have ramifications for potential devices operating at high concentrations, such as polymeric lasers.…”
Section: Discussionsupporting
confidence: 85%
“…Previously, to explain room-temperature measurements of transient absorption in C 60 films exposed to air, an increased rate of T 1 production at high fluence was proposed, but the roles of S 1 and T 1 could not be separated. 19 Recently, a similar preferential growth in T 1 states at high excitation density was reported for the conjugated oligomer para-hexaphenyl. 2 Accompanying the enhanced T 1 production at high excitation densities in C 60 and pp-C 60 , we find complex transient behavior, which includes an increase in the decay rates of both T 1 and S 1 with excited state concentration, always with S 1 decaying more rapidly.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Using a 2.03 eV pump beam and pulse duration of 100 fs, Thomas et al measured the relaxation of photoexcited states in C 60 by time-resolved optical absorption and found a 1 ps response, and when tuning to the forbidden h 1u to t 1u transition, they found a 2 ps relaxation. 4 Ishihara et al used a 100 fs, 0.2 mJ, and 628 nm laser to find that the decay times of the self-trapped exciton and polaron are about 570± 120 fs and 54± 7 ps, but no clear lattice vibration was resolved. 5 A systematic investigation was done by Chergui's group on the ultrafast intramolecular relaxation, where they found that the transient absorption spectra of C 60 have a characteristic rise time of 200 fs.…”
Section: Introductionmentioning
confidence: 99%
“…27 The photoinduced absorption (PIA) in the range of 520−700 nm is ascribed to the S 1 −S n transition. 27,50,51 The negative signal at around 500 nm has been explained as a superposition of PIA and GSB. 27 Let us now focus on the planar mixed heterojunction with a configuration of quartz/C 60 (10 nm)/C 60 :PbI 2 (5 nm, weight ratio = 1:5)/PbI 2 (30 nm), which is similar to the structure of our solar cell.…”
Section: Resultsmentioning
confidence: 99%